Mineral chemistry and geothermobarometry of gabbroic rocks from the Gysel area, Alborz mountains, north Iran (Nexo Revista Científica, 2020)
The gabbroic rocks in the Gysel area of the Central Alborz Mountains in north Iran are intruded into the Eocene Volcano-sedimentary units. The main gabbroic rocks varieties include gabbro porphyry, olivine gabbro, olivine dolerite and olivine monzo-gabbro. The main minerals phases in the rocks are plagioclase and pyroxene and the chief textures are sub-hedral granular, trachytoidic, porphyritic, intergranular and poikilitic. Electron microprobe analyses on minerals in the rock samples shows that plagioclase composition ranges from labradorite to bytonite, with oscillatory and normal chemical zonings. Clinopyroxene is augite and orthopyroxene is hypersthene to ferro-hypersthene. Thermometry calculations indicate temperatures of 650˚C to 750˚C for plagioclase crystallization and 950˚C to 1130˚C for pyroxene crystallization. Clinopyroxene chemistry reveals sub-alkaline and calc-alkaline nature for the parental magma emplaced in a volcanic arc setting.